2018
DOI: 10.1002/adsc.201800405
|View full text |Cite
|
Sign up to set email alerts
|

Unsymmetrical Disulfide Synthesis through Photoredox Catalysis

Abstract: A facile and eco‐friendly visible light‐mediated synthesis of symmetrical and unsymmetrical disulfides using tris[2‐phenylpyridinato‐C2,N]iridium(III) under additive and oxidant free conditions has been disclosed. The developed method is very mild, several functional group tolerant and highly atom economical requiring extremely low amount of catalyst loading (0.5 mol%).magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 63 publications
4
42
0
1
Order By: Relevance
“…[16] In Figure 1a,f ew examples of either pharmaceutically important or naturallyo ccurring molecules containing disulfides functionalities are shown. [28] Similarly,u nsymmetrical disulfide synthesis is also reported using O 2 as the oxidant and cobalt(II)phthalocyanine-tetra-sodium sulfonate as the catalyst (Figure 1b). Recently Dethe and co-workersd eveloped synthesis of unsymmetrical disulfides using fac-Ir(ppy) 3 as photocatalyst and visible light from white LED (Figure 1b).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…[16] In Figure 1a,f ew examples of either pharmaceutically important or naturallyo ccurring molecules containing disulfides functionalities are shown. [28] Similarly,u nsymmetrical disulfide synthesis is also reported using O 2 as the oxidant and cobalt(II)phthalocyanine-tetra-sodium sulfonate as the catalyst (Figure 1b). Recently Dethe and co-workersd eveloped synthesis of unsymmetrical disulfides using fac-Ir(ppy) 3 as photocatalyst and visible light from white LED (Figure 1b).…”
mentioning
confidence: 77%
“…[16b] The known approaches for the synthesis of disulfides are mainly based on using molecular oxygen, [17] transition metals, [18] phosphine-free cationic rhodium(I) complex catalyst, [19] Cu I -phenanthroline catalyst, [20] base catalyzed, [21] non-transition metals, [22] oxidants, [23] sodium perborate, [24] metal organicf rame works (MOFs), [25] microwavea ssisted, [26] electrochemical methods, [27] etc. [28] Similarly,u nsymmetrical disulfide synthesis is also reported using O 2 as the oxidant and cobalt(II)phthalocyanine-tetra-sodium sulfonate as the catalyst (Figure 1b). [28] Similarly,u nsymmetrical disulfide synthesis is also reported using O 2 as the oxidant and cobalt(II)phthalocyanine-tetra-sodium sulfonate as the catalyst (Figure 1b).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…[3] Although many different methods exist for the preparation of unsymmetrical disulfides, the most common approach involves substitution of a sulfenyl derivative with a thiol or thiol derivative. Recently, the oxidation of a mixture of two different thiols by 2,3-dichloro-5,6-dicyanobenzoquinone (DDQ) [29] or iridium (III) photoredox catalysis [30] to produce an unsymmetrical disulfide have also been reported. [22] Other practical procedures involve the reaction of a thiol with a sulfinylbenzimidazole, [23] a rhodium-catalyzed disulfide exchange, [24] an electrochemical method, [25] the ring opening of an aziridine using tetrathiomolybdate in the presence of a symmetrical disulfide, [26] or the use of diethyl azodicarboxylate (DEAD) [27] or a solid support [28] in a sequential coupling of two different thiol groups.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Other practical procedures involve the reaction of a thiol with a sulfinylbenzimidazole, [23] a rhodium-catalyzed disulfide exchange, [24] an electrochemical method, [25] the ring opening of an aziridine using tetrathiomolybdate in the presence of a symmetrical disulfide, [26] or the use of diethyl azodicarboxylate (DEAD) [27] or a solid support [28] in a sequential coupling of two different thiol groups. Recently, the oxidation of a mixture of two different thiols by 2,3-dichloro-5,6-dicyanobenzoquinone (DDQ) [29] or iridium (III) photoredox catalysis [30] to produce an unsymmetrical disulfide have also been reported. Earlier studies demonstrated the preparation of functionalized unsymmetrical molecules, such as dialkyl disulfides, [31] alkyl-aryl disulfides, [32] 'bioresistant' disulfides, [33] unsymmetrical disulfides of L-cysteine and L-cystine, [34] and diaryl disulfides [35] based on the readily available 5,5-dimethyl-2-thioxo-1,3,2-dioxaphosphorinane-2-disulfanyl derivatives.…”
Section: Introductionmentioning
confidence: 99%